Investigating the effect of a raised cycle track, physical separation, land use and number of pedestrian on cyclists’ gaze behavior - Jang, Gukhwa; Kim, Saehoon (Journal of Architecture and Urbanism, 2019)
Contemporary cities are home to an increasing number of cyclists. The gaze behavior of cyclists has an important impact upon cyclist safety and experience. Yet this behavior has not been studied to access its potential implications for urban design. This study aims to identify the eye-gaze pattern of cyclists and to examine its potential relationships with urban environmental characteristics, such as a raised cycle track, physical separation, land use, and number of pedestrian. This study measured and analyzed 40 cyclist’s gaze patterns using an eye tracker; the results were as follows. First, cyclists presented a T-shaped gaze pattern with two spots of frequent eye fixation points; the pattern suggests that it may benefit cyclists with greater safety and better readiness of road situation to avoid crashes. Second, more active horizontal gaze dispersion within the T-shaped gaze pattern was observed when participants cycled on a shared and non-raised bikeway. This indicates that there is a more suitable gaze behavior with different gaze limitations depending on the environmental characteristics. Therefore, bicycle facilities need to be constructed according to the consideration of the T-shaped gaze area and the change in cyclists’ gaze behavior in each environment to increase the effectiveness of bicycle facilities.